2013
DOI: 10.5511/plantbiotechnology.13.0128c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of indole derivatives as potential intermediates of auxin biosynthesis in Arabidopsis

Abstract: Biosynthesis of indole-3-acetic acid (IAA) is crucial for the regulation of plant growth and morphological changes. However, the pathways of IAA biosynthesis have not been completely understood. Although indole derivatives have been proposed to be intermediates of the pathway, it has not been thoroughly elucidated whether the proposed intermediates are indeed converted into an active auxin, IAA, or intermediate metabolites other than IAA. In the present work, we examined 11 indole derivatives whether they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We previously demonstrated that the expression of auxin‐responsive genes was downregulated as a result of auxin deficiency caused by treatment with an inhibitor of auxin biosynthesis (Soeno et al ., ; Ishida et al ., ). Thus, to investigate the effects of inhibitors on auxin signaling, we analyzed expression levels of the auxin‐responsive Aux / IAA1 and Aux / IAA5 genes in response to treatment with KOK1169, AOPP and PEO‐IAA.…”
Section: Resultsmentioning
confidence: 97%
“…We previously demonstrated that the expression of auxin‐responsive genes was downregulated as a result of auxin deficiency caused by treatment with an inhibitor of auxin biosynthesis (Soeno et al ., ; Ishida et al ., ). Thus, to investigate the effects of inhibitors on auxin signaling, we analyzed expression levels of the auxin‐responsive Aux / IAA1 and Aux / IAA5 genes in response to treatment with KOK1169, AOPP and PEO‐IAA.…”
Section: Resultsmentioning
confidence: 97%
“…One of the most important phytohormones, indole acetic acid (IAA), controls cell growth and division [ 106 ]. The plant-derived IAA is also produced by soil and endophytic microorganisms and has been shown to enhance plant development [ 107 , 108 ]. Endophytic fungi, such as Curvularia species, have recently been found to produce IAA in the tissues of aerial plant parts [ 109 ].…”
Section: Application Of Cochliobolus Cu...mentioning
confidence: 99%
“…Other study showed Bacillus subtilis LK14 isolated from Moringa peregrine plant produced auxin hormones that can improved the growth of Solanum lycopersicum [21]. Auxin hormones were known to play important role in cell elongation, division and enlargement [22] and GA could stimulated the shoot length, chlorophyll contents and increased biomass of rice plant [23]. Interestingly, B. amyloliquefaciens LKM-UL isolated from cocoa plant have the ability to produce multiple types of auxins (1-naphthalene acetic acid, tryptamine, 3-indole propionic acid and indole-3-butyric acid), gibberellic acid and cytokinins (trans-zeatin and kinetin).…”
Section: International Journal Of Bioscience Biochemistry and Bioinfmentioning
confidence: 99%